PENDIDIKAN ISLAM DAN TUNTUTAN ZAMAN - Yuanda Kusuma (STAI Ma'had Aly Al-Hikam Malang, 2014)
Islam presented a faith, science, and morality based civilization. A civilization that can‘t be separated from the role of education. As education is to develop the human potency; physical potential, creativity potency, taste and will, education constitutes as the lifeblood of civilization. The advancement of Islamic education that took place for a long time between 1 H and 11 H, with the peak of advancement from 3 H to 7 H, indicated that through qualified education Muslims were able to respond to the needs and demands of times. This article attempts to reconcile the Islamic education base and its objectives with world pretension such as globalization.